Memuliakan Tamu dalam Perspektif Hadis: Menjaga Harmoni Sosial di Tengah Perubahan Zaman - M. Fajri Yusuf (Arba: Jurnal Studi Keislaman, 2025)
Islam strongly emphasizes the importance of honoring guests as part of the noble morals exemplified by the Prophet Muhammad. However, in the context of contemporary social life, the practice of honoring guests is often faced with the challenges of social, economic, and lifestyle changes that are increasingly individualistic. This study aims to explore the limitations of honoring guests from the perspective of the hadith and its implications in modern social life. This study uses a qualitative method with a thematic approach to the hadiths related to the limitations, manners, and ethics of honoring guests, combined with an analysis of classical and contemporary literature to provide a more comprehensive understanding. The results of the study show that honoring guests has clear limitations in Islam, including a maximum time of three days, the type of service provided, and the treatment that is by the host's ability. The implications of this discussion in contemporary social life include the importance of maintaining a balance between honoring guests and considering the financial capabilities and social conditions of the host. The contribution of this study is to provide a clearer perspective on the application of the manners of honoring guests in the modern era, as well as how these principles can be applied in building harmonious social relationships amidst changes in community values.